High Refractive Index Ti3O5 Films for Dielectric Metasurfaces *M. Q. M. acknowledges Information Technology University of the Punjab, Lahore, Pakistan for financial support. J. R. acknowledges the financial support by Engineering Research Center Program (NRF-2015R1A5A1037668), I. K. acknowledges global Ph.D. fellowship (NRF-2016H1A2A1906519), and N. R.-H. acknowledges the KRF fellowship (NRF-2017H1D3A1A02011379) through the National Research Foundation of Korea (NRF) funded by the Ministry of Science, ICT and Future Planning (MSIP) of Korean government. (August 2017) - Jalil, Sohail Abdul; Akram, Mahreen; Yoon, Gwanho; Khalid, Ayesha; Lee, Dasol; Raeis-Hosseini, Niloufar; So, Sunae; Kim, Inki; Ahmed, Qazi Salman; Rho, Junsuk; Mehmood, Muhammad Qasim
Abstract : Ti3 O5 films are deposited with the help of an electron beam evaporator for their applications in metasurfaces. The film of subwavelength (632 nm) thickness is deposited on a silicon substrate and annealed at 400°C. The ellipsometry result shows a high refractive index above 2.5 with the minimum absorption coefficient in the visible region, which is necessary for high efficiency of transparent metasurfaces. Atomic force microscopy analysis is employed to measure the roughness of the as-deposited films. It is seen from micrographs that the deposited films are very smooth with the minimum roughness to prevent scattering and absorption losses for metasurface devices. The absence of grains and cracks can be seen by scanning electron microscope analysis, which is favorable for electron beam lithography. Fourier transform infrared spectroscopy reveals the transmission and reflection obtained from the film deposited on glass substrates. The as-deposited film shows high transmission above 60%, which is in good agreement with metasurfaces.